Do Brazilian hospital pharmacists record, document, archive and disseminate their clinical practice? - Néri, Eugenie Desirèe Rabelo (2019)
An exploratory study was conducted to present the approach of Brazilian hospital pharmacists to registering, documenting, archiving and disseminating clinical practice. The data were collected using an electronic questionnaire (n=348). In fact, 97.41% of pharmacists record their clinical practice, out of which 64.01% (n=217) do in electronic form, mainly in private hospitals (p<0.000), in the central, southern and southeastern regions (p=0.040), and by professionals with 1-5 years of experience (p=0.001). The main software used is non-specific to clinical practice: an electronic spreadsheet (47.93%; n=104) and text editor (13.37%; n=29). The archiving of records is performed by 87.61% (n=297) of professionals, where 80.13% (n=238) do so in physical form; however, 77.31% (n=184) of these files are kept for less than the standard recommended time. Documentation in medical records is carried out by 55.17% (n=192) of pharmacists, increasing among those with 1-5 years of clinical practice (p=0.001), and dissemination is performed by 74.71% (n=260) of hospital pharmacists, with a lower frequency in public hospitals (p=0.012) and among professionals with fewer hours dedicated exclusively to clinical pharmacy (p=0.012). These results can undergird the revision of competency-based training programs of Brazilian clinical pharmacists to remain pharmacists as a valuable health team member.